Advances in designs and mechanisms of semiconducting metal oxide nanostructures for high-precision gas sensors operated at room temperature. Issue 3 (15th January 2019) - Li, Zhijie; Li, Hao; Wu, Zhonglin; Wang, Mingkui; Luo, Jingting; Torun, Hamdi; Hu, PingAn; Yang, Chang; Grundmann, Marius; Liu, Xiaoteng; Fu, YongQing
Abstract : A comprehensive review on designs and mechanisms of semiconducting metal oxides with various nanostructures for room-temperature gas sensor applications. Abstract : High-precision gas sensors operated at room temperature are attractive for various real-time gas monitoring applications, with advantages including low energy consumption, cost effectiveness and device miniaturization/flexibility. Studies on sensing materials, which play a key role in good gas sensing performance, are currently focused extensively on semiconducting metal oxide nanostructures (SMONs) used in the conventional resistance type gas sensors. This topical review highlights the designs and mechanisms of different SMONs with various patterns ( e.g. nanoparticles, nanowires, nanosheets, nanorods, nanotubes, nanofilms, etc. ) for gas sensors to detect various hazardous gases at room temperature. The key topics include (1) single phase SMONs including both n-type and p-type ones; (2) noble metal nanoparticle and metal ion modified SMONs; (3) composite oxides of SMONs; (4) composites of SMONs with carbon nanomaterials. Enhancement of the sensing performance of SMONs at room temperature can also be realized using a photo-activation effect such as ultraviolet light. SMON based mechanically flexible and wearable room temperature gas sensors are also discussed. Various mechanisms have been discussed for the enhanced sensing performance, which include redox reactions, heterojunction generation, formation of metal sulfides and the spillover effect. Finally, major challenges and prospects for the SMON based room temperature gas sensors are highlighted.